How do parents experience video triage when seeking care for their acute ill children? A qualitative study in a Danish out-of-hours primary care setting - Linda Huibers; Morten Bondo Christensen; Elisabeth Assing Hvidt; Mette Amalie Nebsbjerg; Katrine Bjørnshave Bomholt (BMJ Open)
Objective The objective is to explore parents’ experiences with telephone contacts to out-of-hours primary care (OOH-PC) that include use of one-way video (video triage).Design A qualitative interview study using Braun and Clarke’s thematic analysis approach.Setting OOH-PC in the Central Denmark Region.Participants A convenience sampling strategy was used to include parents of young children (aged 1–5 years), who received video triage in OOH-PC: nine women and one man aged 31–42 years. Data were collected from 26 April to 23 May 2023.Results Three main themes were developed, each containing two subthemes: Theme 1. Video triage accelerates diagnostic clarity and prompt action, enhancing feeling of safety: Parents experienced that video triage provided faster diagnostic clarification than telephone triage. The visual assessment in video triage reduced uncertainties of describing symptoms and increased the parents’ feeling of safety. Theme 2. Video triage changed the communicative and relational behaviour: Parents found video triage impersonal as it focused on the physical examination. The conversation before activation of video was found important, as it established a feeling of trust and reassurance. Theme 3. Experiences of presence and involvement in video triage: Parents found their active involvement in video triage challenging, as it required divided attention and shared responsibility.Conclusions Our study indicates the importance of paying attention to the changes in communication and consultation processes afforded by the implementation of one-way video triage. One-way video triage is experienced as a valuable tool for examination, yet it is also perceived to impair the building of trust in the patient–physician relationship.